AKUNTABILITAS PUBLIK PENGADAAN BARANG/JASA PEMERINTAH SECARA ELEKTRONIK (E-PROCUREMENT) DI PEMERINTAH DAERAH DAERAH ISTIMEWA YOGYAKARTA - Yanuar Siswo Nugroho; Zulkifli Zulkifli (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2019)
E-Procurement has animportant role in the implementation of development. Although the e-Procurement in the regional government of the special region of Yogyakarta has been done, however, it is often an instrument that is theoretically good, but in its implementation still has weaknesses and obstacles.The aim of this research is to analyze public accountability of e-Procurement. The instrument that used in this study is accountability dimensions of Koppell and the principles of procurement of goods or services are based on Presidential Regulation Number 16 of 2018. The object of this research is the e-Procurement in the LPSE and ULP Units in the regional government of the special region of Yogyakarta. This study uses a qualitative approach. The research data was obtained through interviews and documentation studies. The results of the study indicate that the implementation of e-Procurement in the regional government of the special region of Yogyakarta has implemented the principle of effective efficiency and open competition and non-discriminatory. The achievement of public accountability in the implementation of e-Procurement in the regional government of the special region of Yogyakarta in general has also been going well.